Increasing Knowledge and Attitudes About HIV/AIDS and the Impact of Free Sex Through Counseling at MTs Darul Ulum, Sasa City of Ternate - Sitti Nurhidayanti Ishak; Hairudin La Patilaiya; Nurhalisa Sahbudin (International Journal Of Community Service, 2022)
The case of HIV/AIDS is a serious problem in several countries, including Indonesia. The government has done a lot of handling by way of counseling and assistance to suppress this problem. One of the parties who play a major role in this response is the school where many teenagers spend their time in the school environment. For this reason, this program aims to increase the knowledge and attitudes of students at MTs Darul Ulum, Sasa sub-district, Ternate city about HIV/AIDS, as well as the impact of the risks of having premarital sex. This service begins with observing the location and making a schedule. Furthermore, the service team conducted counseling at the Darul Ulum MTs school, Sasa sub-district, Ternate city which was attended by teachers and school students. The results of this service can increase students' knowledge and attitudes about the dangers of HIV/AIDS and the impact of free sex behavior. This can be seen from the enthusiasm of the students and the two-way discussion with the students. This program is expected to run sustainably so that the vision, mission, and goals of education can be achieved properly.